ISLAM DAN PLURALISME AGAMA - ., Suyitno (Universitas Muhammadiyah Ponorogo, 2014)
The essence of religious truth genuinely is found in its answer for human problem. For every religion has its own secret mission to save and guide human beings to the good and right way. Pluralism is a reality happens around our daily lives. It appears in terms of religious, cultural, and educational pluralism, race and ethnic. All kinds of pluralism are natural things without any kind of engineering or human desire. It means that it's God's wish as the only creator of human beings and all lives in this world. Of course, on the purpose that people can find within all differences the positive sides as guidance for cooperation, introspection, and help for each other. So that, basically the pluralism values have strong roots in religious teaching, especially Islam whose reality and history are closely related to monotheism as a basic teaching in Islam. In this case, if only Allah wished, all people become one ummah, one ethnic, one nation, one religion, however Allah does not wish so. Intentionally, Allah created us in different kinds to examine whatHe has given and let His servants compete each other in good deeds.